Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-019-57377-9
|View full text |Cite
|
Sign up to set email alerts
|

Female Reproductive Performance and Maternal Birth Month: A Comprehensive Meta-Analysis Exploring Multiple Seasonal Mechanisms

Abstract: Globally, maternal birth season affects fertility later in life. The purpose of this systematic literature review is to comprehensively investigate the birth season and female fertility relationship. Using PubMed, we identified a set of 282 relevant fertility/birth season papers published between 1972 and 2018. We screened all 282 studies and removed 131 non-mammalian species studies on fertility and 122 studies that were on non-human mammals. Our meta-analysis focused on the remaining 29 human studies, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
5
0
1
Order By: Relevance
“…We were not able to distinguish whether these are independent effects or whether they arise because of the co-linearity with the climatic variables. In both cases, however, there is a combined mechanism at work between temperature and rainfall, as found by others [3]. In this sense, temperature might not correlate directly with conceptions and births (via biological or behavioural mechanisms) but it might have a role in controlling other variables that do affect the reproductive pattern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We were not able to distinguish whether these are independent effects or whether they arise because of the co-linearity with the climatic variables. In both cases, however, there is a combined mechanism at work between temperature and rainfall, as found by others [3]. In this sense, temperature might not correlate directly with conceptions and births (via biological or behavioural mechanisms) but it might have a role in controlling other variables that do affect the reproductive pattern.…”
Section: Discussionmentioning
confidence: 86%
“…the seasonality of conception and birth, is of importance because birth months have significant consequences for many demographic aspects such as infant mortality [e.g. 1 , 2 ], maternal performance [ 3 ], adult height [ 4 ], lifespan [ 5 , 6 ] and susceptibility to late-onset diseases [e.g. 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This enabled us to develop a method that correlated birth season and trimester information with climate and pollution variables using location information 34 . We have also used our methods to study the effects of social exposures that can manifest as birth month relationships for Attention Deficit Hyperactivity Disorder (ADHD) 35 and increased the number of datasets included in our assessment of female fertility and birth season to assess deeper and more complex multi-factorial environmental exposures 36 . We have found that prenatal exposure to fine air particulates increased the risk of atrial fibrillation later in life in humans 34 ; this finding was supported by a study in a canine population 37 .…”
Section: Impactmentioning
confidence: 99%
“…In addition, a number of unusual weather events have affected the quality of life of people around the world, posing challenges to the health systems of many countries (2). For example, rates of diarrhea and vector-borne diseases have increased in tropical locations and hot climate regions (3,4), also affecting the reproductive output of affected populations (5).…”
Section: Introductionmentioning
confidence: 99%